Westonci.ca offers fast, accurate answers to your questions. Join our community and get the insights you need now. Connect with professionals ready to provide precise answers to your questions on our comprehensive Q&A platform. Explore comprehensive solutions to your questions from knowledgeable professionals across various fields on our platform.

Write an equation of a circle that is centered at [tex]\((-3, 2)\)[/tex] with a radius of 5.

A. [tex]\((x-3)^2 + (y+2)^2 = 5\)[/tex]

B. [tex]\((x+3)^2 + (y-2)^2 = 5\)[/tex]

C. [tex]\((x-3)^2 + (y+2)^2 = 25\)[/tex]

D. [tex]\((x+3)^2 + (y-2)^2 = 25\)[/tex]


Sagot :

To determine the equation of a circle given the center and the radius, we use the standard form of the equation of a circle:

[tex]\[ (x - h)^2 + (y - k)^2 = r^2 \][/tex]

where [tex]\((h, k)\)[/tex] is the center of the circle and [tex]\(r\)[/tex] is the radius.

Given:
- The center of the circle is [tex]\((-3, 2)\)[/tex]
- The radius of the circle is [tex]\(5\)[/tex]

First, let's substitute the given center [tex]\((-3, 2)\)[/tex] into the general equation. Here, [tex]\(h = -3\)[/tex] and [tex]\(k = 2\)[/tex]:

[tex]\[ (x - (-3))^2 + (y - 2)^2 = r^2 \][/tex]

Simplify the expression inside the parentheses:

[tex]\[ (x + 3)^2 + (y - 2)^2 = r^2 \][/tex]

Next, we substitute the given radius [tex]\(r = 5\)[/tex] into the equation:

[tex]\[ (x + 3)^2 + (y - 2)^2 = 5^2 \][/tex]

Since [tex]\(5^2 = 25\)[/tex], the equation becomes:

[tex]\[ (x + 3)^2 + (y - 2)^2 = 25 \][/tex]

Thus, the correct equation of the circle is:

[tex]\[ (x + 3)^2 + (y - 2)^2 = 25 \][/tex]

Therefore, the correct answer is [tex]\(D\)[/tex]:
[tex]\[ (x + 3)^2 + (y - 2)^2 = 25 \][/tex]
Thank you for trusting us with your questions. We're here to help you find accurate answers quickly and efficiently. We appreciate your visit. Our platform is always here to offer accurate and reliable answers. Return anytime. Your questions are important to us at Westonci.ca. Visit again for expert answers and reliable information.